ANÁLISE DAS HABITAÇÕES DE INTERESSE SOCIAL NO MUNICÍPIO DE JUNDIAÍ/SP APÓS A EXTINÇÃO DO BANCO NACIONAL DE HABITAÇÃO (BNH) - Guimarães, Janayna; Debiazi, Pedro (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The objective of this research of Scientific Initiation is to identify and to analyze the diverse productions of Housing of Social Interest (HIS) realized in the city of Jundiaí, between the years of 1986 and 2017, with main focus in the enterprises after the implantation of the Programa Minha Casa Minha Vida (PMCMV). The research is guided by bibliographical revision, survey and analysis of data and documents and creation of thematic maps. The diagnoses and reflections obtained from this research will contribute to chronologically recognize and contextualize the current housing scenario of the municipality and the influences suffered by the different housing programs implemented in Jundiaí, orienting the decision making of the planners and the public power to projects of new housing developments.